Annexin A6 regulates adipocyte lipid storage and adiponectin release. (5th January 2017) - Krautbauer, Sabrina; Haberl, Elisabeth M.; Eisinger, Kristina; Pohl, Rebekka; Rein-Fischboeck, Lisa; Rentero, Carles; Alvarez-Guaita, Anna; Enrich, Carlos; Grewal, Thomas; Buechler, Christa; Neumeier, Markus
Abstract: Lipid storage and adipokine secretion are critical features of adipocytes. Annexin A6 (AnxA6) is a lipid-binding protein regulating secretory pathways and its role in adiponectin release was examined. The siRNA-mediated AnxA6 knock-down in 3T3-L1 preadipocytes impaired proliferation, and differentiation of AnxA6-depleted cells to mature adipocytes was associated with higher soluble adiponectin and increased triglyceride storage. The latter was partly attributed to reduced lipolysis. Accordingly, AnxA6 overexpression in 3T3-L1 adipocytes lowered cellular triglycerides and adiponectin secretion. Indeed, serum adiponectin was increased in AnxA6 deficient mice. Expression analysis identified AnxA6 protein to be more abundant in intra-abdominal compared to subcutaneous adipose tissues of mice and men. AnxA6 protein levels increased in white adipose tissues of obese mice and here, levels were highest in subcutaneous fat. AnxA6 protein in adipocytes was upregulated by oxidative stress which might trigger AnxA6 induction in adipose tissues and contribute to impaired fat storage and adiponectin release. Highlights: Annexin A6 (AnxA6)-depleted adipocytes have increased triglycerides and adiponectin. Serum adiponectin is increased in AnxA6 deficient mice. AnxA6 in 3T3-L1 adipocytes is upregulated by oxidative stress. AnxA6 is induced in white adipose tissues of mice fed a high fat diet.